Postoperative adjustment of implanted Corneal Allogeneic Intrastromal Ring Segments (CAIRS) to improve visual and topographic outcomes - Jacob, Soosan; Agarwal, Amar; Awwad, Shady T.; Son, Hyeck Soo; Auffarth, Gerd U.; Abraham, Riya; Narasimhan, Smita (Journal of refractive surgery, 2025)
PURPOSE: To report adjustment of different corneal allogeneic intrastromal ring segments (CAIRS) parameters in a group of patients with suboptimal visual and topographic results. METHODS: Thirteen eyes of 13 patients with suboptimal first-stage outcomes in the form of a decrease or lack of improvement in uncorrected (UDVA) or corrected (CDVA) distance visual acuity or complaining of decreased visual quality together with worsening of topographic map were included in this retrospective interventional case series. Adjustment was performed for arc length, width, thickness, placement, or optical zone. RESULTS: Post-implantation (Intervention-1) mean improvement in UDVA and CDVA compared to preoperatively was 1.5 +/- 3 (range: 6 to 3) and 0.2 +/- 1.5 (range: 2.5 to 3) lines of vision, respectively. Three lines of UDVA and 0.5 to 3 lines of CDVA were lost in 2 and 5 patients, respectively. Post-adjustment (Intervention-2) mean improvement in UDVA and CDVA compared to preoperatively was 3.6 +/- 3 (range: 10 to 0) and 1.15 +/- 1.6 (range: 5.5 to 0) lines, respectively. No patient lost any lines of UDVA or CDVA after adjustment. All patients who lost lines after Intervention-1 regained it after adjustment. The Friedman chi-squared test showed a global difference across the three time points for UDVA, CDVA, spherical equivalent (SE), refractive astigmatism (RA), keratometry (steep [Ksteep], flat [Kflat], and mean [Kmean]) (chi-square = 11.7 to 16.8, P <= .003). Bonferroni-corrected Wilcoxon tests showed significant improvements for UDVA, SE, RA, Ksteep, Kflat, Kmean, and maximum keratometry (Kmax) between different time points. Before Intervention-1 to after Intervention-2 contrast yielded smaller P values than before Intervention-1 to after Intervention-1 for all parameters, thus showing larger improvements. Kmax showed a statistically significant difference but was not considered important because Kmax after CAIRS implantation is often outside the visual axis. CONCLUSIONS: Adjustments are possible to try and improvesuboptimal results after CAIRS implantation.